Laparoscopic cholecystectomy. Experience of the Italian Hospital team. Analysis of the first 79 cases - Praderi Gambardella, Luis A; Tchekmedyian, Vartan; Voelker, Ricardo; Balboa, Oscar; Geninazzi, Héctor; Matteucci, Pablo; Praderi, Luis A (Cirugía del Uruguay, 1992)
The experience on the first 79 cases of laparoscopic cholecystectomy performed between March and October 1991 at the Hospital Italiano is presented. Details of the technique. indications, counterindications and resu/ts are analysed. A scheme far study and treatment is proposed for patients suspect of lithiasis of the main biliary viae who are candidates for this type of surgery. lt is concluded that this new surgical approach far cholecystectomy, according to the obtained results, presents varoious advantages. specially as regards decrease in parietal aggression. mínima! postoperative pain, brief hospitalization and quick return to work. This encourages work along this line. with additional projection to other territories of abdominal surgery.